Collaborative Governance in Local Development Planning for Annual Local Work Planning in Karangasem Regency, Bali, Indonesia - I Made Sugiartha; Tjahya Supriatna; M Irwan Tahir; Ika Sartika (Yayasan Riset dan Pengembangan Intelektual, 2023)
Law Number 25 of 2004, mandates that the National Development Planning system (SPPN) is a unified development planning procedure to produce long-term, medium-term and annual development plans, which are implemented by state administrators at the central and regional levels. The Karangasem Regency Government's Vision and Mission, which has been outlined in the Karangasem Regency RPJMD, is described into Programs, Activities and Sub-Activities implemented by Regional Apparatus. The implementation of Programs and Activities by each Regional Apparatus, each Fiscal Year must be accounted for. The performance of the Karangasem Regency Government in terms of geographic and demographic aspects, community welfare aspects, public service aspects, and competitiveness aspects, the budget allocated and the performance achievements obtained, have not yet been fully realized optimally. Planning as an element of management plays an important role in achieving the goals of an organization. The theory used in this research is the Collaborative Governance Theory, which suggests the importance of collaboration between related parties in regional development planning. Using Qualitative Methods, this research aims to determine the Collaborative Governance of Regional Development Planning in Karangasem Regency, Bali Province. Through Soft Strategy Mathematics Analysis, it is known that Collaborative Governance between Government, Academics, Private and Community needs to be optimized. By adding one indicator to each dimension in the Collaborative Governance Theory, a model is then recommended that can be used in regional development planning in Karangasem Regency, Bali Province.